Observed changes in mineralization of atmospheric precipitation in the territory of Kazakhstan - Kurmanova, M.S.; Madibekov, A.S. (Fundamental and Experimental Biology, 2022)
The article presents the main results of the study of mineralization of atmospheric precipitation in the territory of the Republic of Kazakhstan. It has been established that there is a tendency in the territory of some lakes as a sharp decrease, as well as an increase in the mineralization of atmospheric precipitation. Statistically signifi-cant increasing in mineralization of precipitation was observed near the lakes Shalkar (Aktobe region), Markakol, and the tendency to decrease is observed in the lakes of Balkhash (western part), Bilikol, Ulken, Kishi Shabakty. Precipitation is the main factor in the formation of surfaceand groundwater. Due to climatic and orographic features of Kazakhstan, there is an uneven distribution of precipitation in the territory. A sig-nificant part of the country, with the exception of mountainous areas, suffers from a deficit of atmospheric precipitation. In geochemistry, the study of the chemical composition of atmospheric precipitation describes the exchange of salts between the atmosphere, the earth’s surface, and the sea. Knowledge of the chemical composition of precipitation is necessary for sanitary and hygienic purposes in order to know the nature of air pollution in industrial zones. According to the program of the World Meteorological Organization (WMO), precipitation samples are collected for the following substances, such as: anions —sulfates, chlorides, nitrates; cations —ammonium, sodium, potassium, calcium, magnesium; heavy metals —lead, copper, cadmium, arsenic, acidity and specific gravity. The knowledge of different mixtures of atmospheric precipitation has an important value for agrochemists, hydrochemists, hydrogeologists and geochemists for the study of natural and surface waters, the surface of the soil, as well as for the preventive measures.